ASSESSMENT OF BAMBOO-BASED ANTI-HAILSTORM STRUCTURES: EVALUATING STABILITY AND RESILIENCE AGAINST RAINFALL, WIND, AND HAIL EVENTS (CAHIERS MAGELLANES-NS, 2024)
The purpose of this research is to determine how well bamboo-based anti-hailstorm structures provide stability and resilience in the face of a variety of unfavorable weather conditions, such as wind, rain, and hail events. The study also aims to investigate the benefits that using bamboo as a primary construction material has for the environment, as well as the structural integrity and material durability. Software analysis and simulations were used to evaluate the performance of these structures under simulated hailstorms, heavy rainfall, and high wind speeds. The results show that bamboo, because of its strength and flexibility, offers a viable, sustainable alternative to conventional materials.